2017
DOI: 10.1073/pnas.1620736114
|View full text |Cite
|
Sign up to set email alerts
|

Gene–culture coevolution in whales and dolphins

Abstract: Whales and dolphins (Cetacea) have excellent social learning skills as well as a long and strong mother-calf bond. These features produce stable cultures, and, in some species, sympatric groups with different cultures. There is evidence and speculation that this cultural transmission of behavior has affected gene distributions. Culture seems to have driven killer whales into distinct ecotypes, which may be incipient species or subspecies. There are ecotypespecific signals of selection in functional genes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 80 publications
0
60
0
2
Order By: Relevance
“…Cultural transmission also has large-scale evolutionary implications for some nonhuman animals: For example, theoretical studies suggest that nonrandom mating in birds based on culturally transmitted songs could accelerate speciation (180,181) and that sexual selection on learned songs could influence evolution of the neural underpinnings of learning (182). Recently, studies in a range of animal species have shown that cultural practices can emerge, spread, and change over time, potentially influencing individuals' fitness (183)(184)(185)(186)(187). Tool use among chimpanzees and capuchins (188)(189)(190)) is one such example, which also provides insight regarding the possible origins of the early phases of our own species' adaptation to the "cultural niche" (191,192).…”
Section: Discussionmentioning
confidence: 99%
“…Cultural transmission also has large-scale evolutionary implications for some nonhuman animals: For example, theoretical studies suggest that nonrandom mating in birds based on culturally transmitted songs could accelerate speciation (180,181) and that sexual selection on learned songs could influence evolution of the neural underpinnings of learning (182). Recently, studies in a range of animal species have shown that cultural practices can emerge, spread, and change over time, potentially influencing individuals' fitness (183)(184)(185)(186)(187). Tool use among chimpanzees and capuchins (188)(189)(190)) is one such example, which also provides insight regarding the possible origins of the early phases of our own species' adaptation to the "cultural niche" (191,192).…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of laboratory experimental studies have demonstrated social learning and transmission in a wide variety of animals. Social learning is now extensively documented in mammals (29), with a particular intensity of research studies in primates (30)(31)(32)(33) and cetaceans (34)(35)(36)(37), in birds (38)(39)(40)(41), in fish (42), and in insects (43,44). The fact that social learning has been shown to play important roles spanning multiple functional contexts (25)(26)(27)(28) suggests that many animals are not simply acquiring one or a few behavioral patterns socially, but rather that social learning is central to their acquisition of adaptive behavior.…”
Section: The Discovery Of Widespread Animal Culturementioning
confidence: 99%
“…The most comprehensive analyses of such effects in cultural evolution among animals have been in whales and dolphins (34,35). In some species, different migratory routes appear to be culturally transmitted from mothers to calves, thence reflected in diverging genetic make-ups.…”
Section: How Culture Extends Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…But discoveries in recent decades suggest that a wide range of cultural practices-from foraging tactics and vocal displays to habitat use and play-may influence the lives of other animals as well (3). Studies attribute additional orca behaviors, such as migration routes and song repertoires, to culture (4). Other research suggests that a finch's song (5), a chimpanzee's nut cracking (3), and a guppy's foraging route (6) are all manifestations of culture.…”
mentioning
confidence: 99%